ANALISIS PENYAMBUNGAN PLTS OELPUAH 5 MWP KE SISTEM SALURAN UDARA TEGANGAN MENENGAH (SUTM) 20 KV PT. PLN UNIT LAYANAN KUPANG - Frans Likadja; Wellem F. Galla; Dian Cornalia Kase (Jurnal Media Elektro, 2022)
This study aims to examine the impact of connecting PLTS Oelpuah with a capacity of 5 MW to SUTM 20 kV, in terms of the power flow and the magnitude of the change in voltage, generation composition, and electric power factor, when PLTS works in sunny, cloudy, and rainy weather conditions, and how the conditions system with and without the operation of PLTD LMVPP. From the results of the analysis obtained, the voltage profile at the point of connection of the Oelpuah PLTS to the Oesao feeder and the Undana Substation varies depending on weather conditions. When the weather is sunny, the voltage at the Undana substation and the Oesao feeder is stabel, but when the weather is cloudy and rainy, the distribution voltage at the Oesao feeder and the Undana feeder decreases. The composition of the generator's power supply has also changed due to weather conditions. When it is sunny PLTS supplies 3.2 MW, PLTD LMVPP supplies 12.6 MW, when it is cloudy PLTS supplies 915 kW, PLTD LMVPP supplies 15 MW and when it rains PLTS cannot supply power to the system, and PLTD LMVPP must increase its electrical power supply to 16 MW. When the PLTD LMVPP is separated from the system, any reduction in the power composition of the PLTS due to changing weather is transferred to the PLTU IPP. The electric power factor at the PLTS connection point, namely the Oesao feeder, is also influenced by changing weather conditions.